Effect Momming Guide Kangoroe Mother Care Skin to Skin Contact on the Body Weight on Low Birth Weight - Mendri, Ni Ketut; Badi’ah, Atik; Subargus, Amin (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Babies are children who are in the age range 0–12 months. Infancy is the first phase of human life, which at this time requires adaptation to the environment. Low birth weight (LBW) is a newborn who has a birth weight of <2500 g (up to 2499 g). Babies with LBW will have an impact in the long term in the future that will affect the quality of the nation’s next generation. General management of infants with LBW is very necessary to prevent complications. General management that can be given to infants with LBW is maintaining body weight by weighing daily and monitoring nutritional intake. One of the actions that can be given to babies with LBW is using the Kangaroo Mother Care (KMC) method. KMC method of treatment is a skin to skin contact therapy, namely, conduction heat transfer from mother to baby so that the baby remains warm and stable so that it will increase the baby’s weight. Researchers are interested in taking the title “The Effect of Momming Guide Kanggoroe Mother Care Skin To Skin Contact on Body Weight in LBW in Puskesmas Daerah Istimewa Yogyakarta.” AIM: To find out the effect of Momming Guide Kanggoroe Mother Care Skin To Skin Contact on Body Weight in LBW in Puskesmas Daerah Istimewa Yogyakarta METHODS: Quasi experimental research type with the design of “Pre-test Post-test with Control Group Design.” Sampling was carried out by purposive sampling with the criteria of parents (mothers) who have babies with LBW at the Yogyakarta Special Public Health Center. Data were analyzed analytically using t-test and Wilcoxon with a significant level of 0.05. RESULTS: The difference in the weight of newborns with the 1st month and the 2nd month with the 3rd month there is a difference with the value of p = 0.00 (<0.05). While the difference in body weight in the 1st and 2nd month, there was a difference with p = 0.005 (< 0.05). CONCLUSION: There is an effect of Momming Guide Kanggoroe Mother Care Skin To Skin Contact on Body Weight in LBW in Puskesmas Daerah Istimewa Yogyakarta.